“The Passions of the Soul” by R. Descartes as an Explication of the Anthropological and Ethical Project - Malivskyi, Anatolii; Khmil, Volodymyr (Studia Warmińskie, 2019)
The authors set and solve the task of explication of the anthropological and ethical motive of philosophizing hidden in the Cartesian legacy. At the heart of their approach is the vision of the Modern Age, first of all, as a request for the development of anthropology, the implementation of which in the texts of the thinker is traditionally perceived fragmentarily and superficially. In the course of addressing his writings and the text of “The Passions of the Soul”, the authors defend the thesis of the possibility of their reception and as a manifestation of interest in the integral nature of man. Based upon the earlier texts, the content features of the anthropological position of Descartes in “The Passions of the Soul” are outlined. They include the emphasis on the significance of metaphysics, the focus on freedom of will, the interest in the volitional component of human nature, and the vision of passions as a form of expression of a substantive union of mind and body.